Transfer in der Lehre: Zivilgesellschaftliches Engagement als Zumutung oder Chance für die Hochschulen? - Hoffmeister, Thomas S.; Mühleisen, Sibylle; Kümmel-Schnur, Albert (transcript, 2020)
Do students and teachers experience cooperation with civil society as a blessing or a curse? A survey with numerous practical examples.